Subregional Shape Alterations in the Amygdala in Patients with Panic Disorder. - Sujung Yoon; Jieun E Kim; Geon Ha Kim; Hee Jin Kang; Bori R Kim; Saerom Jeon; Jooyeon Jamie Im; Heejung Hyun; Sohyeon Moon; Soo Mee Lim; In Kyoon Lyoo (PLoS ONE, 2016)
The amygdala has been known to play a pivotal role in mediating fear-related responses including panic attacks. Given the functionally distinct role of the amygdalar subregions, morphometric measurements of the amygdala may point to the pathophysiological mechanisms underlying panic disorder. The current study aimed to determine the global and local morphometric alterations of the amygdala related to panic disorder.Volumetric and surface-based morphometric approach to high-resolution three-dimensional T1-weighted images was used to examine the structural variations of the amygdala, with respect to extent and location, in 23 patients with panic disorder and 31 matched healthy individuals.There were no significant differences in bilateral amygdalar volumes between patients with panic disorder and healthy individuals despite a trend-level right amygdalar volume reduction related to panic disorder (right, β = -0.23, p = 0.09, Cohen's d = 0.51; left, β = -0.18, p = 0.19, Cohen's d = 0.45). Amygdalar subregions were localized into three groups including the superficial, centromedial, and laterobasal groups based on the cytoarchitectonically defined probability map. Surface-based morphometric analysis revealed shape alterations in the laterobasal and centromedial groups of the right amygdala in patients with panic disorder (false discovery rate corrected p < 0.05).The current findings suggest that subregion-specific shape alterations in the right amygdala may be involved in the development and maintenance of panic disorder, which may be attributed to the cause or effects of amygdalar hyperactivation.